Emotional Intelligence as a Theoretical Tool for Enhancing Job Performance - Ali Zghair, Assist. Lect. Sanaa (Basra studies journal, 2026)
This study examines the relationship between emotional intelligence as a theoretical tool and the enhancement of job performance among employees of the Basra Directorate of Education. The study employed a descriptive methodology, relying on a sample of 32 employees from the Basra Directorate of Education. Data were collected through a scientifically designed questionnaire and analyzed using appropriate descriptive and inferential statistical methods. The results indicated that the level of emotional intelligence among the employees was high, with a mean score of 3.77, reflecting strong awareness of emotional and affective aspects. The findings also revealed that the level of job performance within the same sample was similarly high, with a mean score of 3.67. Based on these findings, the study recommends organizing training programs to further develop employees’ emotional intelligence skills.